Immobilization of vaginal Lactobacillus in polymeric nanofibers for its incorporation in vaginal probiotic products - Silva, Jessica Alejandra (2021)
Probiotic products require high number of viable and active microorganisms during storage. In this work, the survival of human vaginal Lactobacillus gasseri CRL1320 and Lactobacillus rhamnosus CRL1332 after nanofiber-immobilization by electrospinning with polyvinyl-alcohol, and during storage was evaluated. The optimization of bacterial immobilization and storage conditions using bioprotectors (skim milk-lactose and glycerol) and oxygen-excluding packaging was carried out, compared with lyophilization. After electrospinning, a higher survival rate of L. rhamnosus (93%) compared to L. gasseri (84%) was obtained in nanofibers, with high viable cells (>107 colony-forming unit/g) of the two probiotics in nanofibers stored at -20°C up to 14 days. The storage in oxygen-excluding packaging was an excellent strategy to extend the shelf-life of L. rhamnosus (up to 1.7 × 108 CFU/g) in nanofibers stored at 4°C during 360 days, with no addition of bioprotectives, resulting similar to freeze-dried-cells. L. rhamnosus was successfully incorporated into polymeric hydrophilic nanofibers with a mean diameter of 95 nm. The composite materials were characterized in terms of morphology, and their physicochemical and thermal properties assessed. Nanofiber-immobilized L. rhamnosus cells maintained the inhibition to urogenital pathogens. Thus, polymeric nanofiber-immobilized L. rhamnosus CRL1332 can be included in vaginal probiotic products to prevent or treat urogenital infections.